Impacts and Countermeasures of Climate Change on Food Supply in Korea - 김창길 (기후변화가 식량공급에 미치는 영향 분석과 대응방안, 2013)
According to the domestic and international agencies specializing in climate change, the Earth’s average temperature is expected to continue rising and thus it has been treated as a core global agenda. While research has uncovered some positive aspects to climate change, the impact on the food supply sector is deeply negative. The effects of climate change in Korea are expected to accelerate in future. Even so, domestic research on climate change in the agricultural sector have been limited to analyses of climate change vis-à-vis its impact on agricultural production and the efficacy of proposed countermeasures. Despite the focus of the research the analysis of climate change impact on food supply and proposal of countermeasures remains quite insufficient. Given Korea’s low food self-sufficiency rate, a systematic analysis of the impacts of climate change on the food supply and the proposed response plans is required. This analysis will provide information necessary for the development of future food policies which have as their goal the realization of a stable food supply system. This report is the final outcome of the KREI master project entitled Impacts and Countermeasures of Climate Change on Food Supply in Korea. In this report, the domestic food production potential is diagnosed taking into account and detailing the domestic and overseas climate change; analysis of the impacts of climate change on food supply; the trends of discussion among international organizations, and case studies on setting forth major countries’ responses, and the plans for developing a stable food supply system in response to the climate change. Four specific action plans for ensuring a future stable food supply system are presented. These action plans deal with four aspects, namely: domestic production capacity, buffering capacity, food import capability and the capability of policy responses. This research is expected to be utilized as the basic data for establishing response strategies by first identifying the impacts of climate change on food supply strategy.